The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1126/science.aaf7810
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde stabilization facilitates lignin monomer production during biomass depolymerization

Abstract: bloom dynamics depend principally on the impact of consumers, a long-recognized control of phytoplankton abundance (30). Our findings for Synechococcus agree with those of Behrenfeld and Boss in so far as division rates (and, by inference, loss rates) are roughly 10 times the accumulation (net growth) rates. Our results differ, however, in that we find a significant positive correlation between division and accumulation rates over the course of the spring bloom (Fig. 4, B and C). This correlation was not detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

33
889
3
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 1,010 publications
(980 citation statements)
references
References 37 publications
33
889
3
2
Order By: Relevance
“…The thermal conversion of lignocellulosics to renewable gas and bio-oils has been heavily researched, and the benefits for industrial implementation have become clear (Yaman, 2004;Saidi et al, 2014). Feedstocks with high lignin levels might be a promising source of aromatic/phenolic compounds to produce bio-based products from lignin, as proposed in a lignin-first biorefinery approach ( Van den Bosch et al, 2015;Rinaldi et al, 2016) and as demonstrated recently with high-level monomer production via hydrogenolysis (Shuai et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The thermal conversion of lignocellulosics to renewable gas and bio-oils has been heavily researched, and the benefits for industrial implementation have become clear (Yaman, 2004;Saidi et al, 2014). Feedstocks with high lignin levels might be a promising source of aromatic/phenolic compounds to produce bio-based products from lignin, as proposed in a lignin-first biorefinery approach ( Van den Bosch et al, 2015;Rinaldi et al, 2016) and as demonstrated recently with high-level monomer production via hydrogenolysis (Shuai et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…By using 2D-NMR in conjunction with methoxyl group analysis, we are able to quantitatively determine where and to what degree bond cleavage is occurring in the wood cell wall, and understand the functional roles of the interactions between the multiple partners in the lignocellulosic pretreatment by fungus-cultivating termites. In fact, 2D-NMR is the most diagnostic approach to ascertain the presence and relative levels of the various units within native lignin (35). We elucidated the relative distributions of the various lignin subunits, characterized by their specific interunit linkages, as well as the polysaccharide profile (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, under these processing conditions the lignin component is structurally modified, rendering its further catalytic valorization very challenging [4][5][6][7] . This remains true despite impressive advances in the selective conversion of lignin model compounds 8,9 and depolymerization of organosolv lignin [10][11][12][13][14] . Recently, elegant research has focused on lignocellulose fractionation in the presence of a catalyst 4,[15][16][17] .…”
mentioning
confidence: 99%